The Paul glaucoma implant: a narrative review and a perspective on design, surgical techniques, and current evidence - Abouhamid, Muhammad Ali; Barton, Keith (Annals of Eye Science, 2026)
Background and Objective: Glaucoma drainage devices (GDDs) have been proven to reduce the intraocular pressure (IOP), especially in refractory glaucoma. In particular, non-valved GDDs have superior proven IOP-lowering efficacy than valved implants. However, this advantage comes at the expense of safety concerns. The Paul glaucoma implant (PGI)—the focus of this article—is a new non-valved GDD, designed in an attempt to narrow this safety-efficacy gap.Methods: A literature search was conducted using PubMed and Google Scholar databases. Search terms used included “Paul glaucoma implant”, “glaucoma drainage device”, and “aqueous shunt”. For reporting PGI outcomes, only peer-reviewed articles published in English by August 2025 that included follow-up duration of at least 12 months were included. Both authors were involved in the selection process and consensus was obtained by discussion.Key Content and Findings: This article provides a perspective on the PGI design and surgical technique of PGI implantation, followed by a narrative review of the currently available evidence of outcomes. Despite the limited numbers and quality of the evidence available, it suggests similar efficacy to previous non-valved GDDs, with greater predictability and hence an improved safety profile, at least in the intermediate term.Conclusions: The unique features of the PGI show some promise in terms of improving the safety efficacy tradeoff for GDD. However, high level evidence regarding outcomes, especially in comparison with conventional well-established GDDs, is still absent.